Assessment of the EarlyCDT‐Lung test as an early biomarker of lung cancer in ever‐smokers: A retrospective nested case‐control study in two prospective cohorts. Issue 9 (5th November 2022) - Wu, Wendy Yi‐Ying; Haider, Zahra; Feng, Xiaoshuang; Heath, Alicia K.; Tjønneland, Anne; Agudo, Antonio; Masala, Giovanna; Robbins, Hilary A.; Huerta, José‐María; Guevara, Marcela; Schulze, Matthias B.; Rodriguez‐Barranco, Miguel; et al.
Abstract: The EarlyCDT‐Lung test is a blood‐based autoantibody assay intended to identify high‐risk individuals for low‐dose computed tomography lung cancer screening. However, there is a paucity of evidence on the performance of the EarlyCDT‐Lung test in ever‐smokers. We conducted a nested case‐control study within two prospective cohorts to evaluate the risk‐discriminatory performance of the EarlyCDT‐Lung test using prediagnostic blood samples from 154 future lung cancer cases and 154 matched controls. Cases were selected from those who had ever smoked and had a prediagnostic blood sample <3 years prior to diagnosis. Conditional logistic regression was used to estimate the association between EarlyCDT‐Lung test results and lung cancer risk. Sensitivity and specificity of the EarlyCDT‐Lung test were calculated in all subjects and subgroups based on age, smoking history, lung cancer stage, sample collection time before diagnosis and year of sample collection. The overall lung cancer odds ratios were 0.89 (95% CI: 0.34‐2.30) for a moderate risk EarlyCDT‐Lung test result and 1.09 (95% CI: 0.48‐2.47) for a high‐risk test result compared to no significant test result. The overall sensitivity was 8.4% (95% CI: 4.6‐14) and overall specificity was 92% (95% CI: 87‐96) when considering a high‐risk result as positive. Stratified analysis indicated higher sensitivity (17%, 95% CI: 7.2‐32.1) in subjects with blood drawn up to 1 year prior to diagnosis. In conclusion, our study does not support a role of the EarlyCDT‐Lung test in identifying the high‐risk subjects in ever‐smokers for lung cancer screening in the EPIC and NSHDS cohorts. Abstract : What's new? Low‐dose computed tomography (LDCT) is a promising tool for the early detection of lung cancer. To improve its effectiveness, prescreening to identify individuals with high lung cancer risk may be necessary. Here, the authors examined the prescreening utility of the commercially available blood‐based autoantibody EarlyCDT®‐Lung test. Analysis of prediagnostic blood samples from cases and controls reveals low sensitivity for the EarlyCDT®‐Lung test, with limited evidence supporting an association between a positive test result and lung cancer risk. The results indicate that the EarlyCDT®‐Lung test is unlikely to be useful for identifying ever smokers with an elevated risk of lung cancer.